Faktor eksternal yang mempengaruhi academic self-efficacy: Sebuah tinjauan literatur - Chozina Nauvalia (Fakultas Psikologi, 2021)
Academic self-efficacy is one’s belief in his/her ability to do assignments, regulate their learning activities, or realize their academic expectations. Indeed, a great level of academic efficacy is needed by one student so he or she can meet his/her academic expectations. The purpose of this study was to examine the results of research related to external factors affecting academic self-efficacy. Literature identification was conducted on databases such as google scholar, Science direct, SAGE Journals, and Springerlink using the keywords ”efikasi diri akademik”, ”academic self-efficacy”, and ”academic self-efficacy factors”. The results of this study found that family factors, friendship factors, and teacher support factors are external factors that can affect the level of individual’s academic self-efficacy.